Resting heart rate as a predictor of metabolic dysfunctions in obese children and adolescents - Freitas Junior, Ismael F. [UNESP]; Monteiro, Paula A. [UNESP]; Silveira, Loreana S. [UNESP]; Cayres, Suziane U. [UNESP]; Antunes, Barbara M. [UNESP]; Bastos, Karolynne N. [UNESP]; Codogno, Jamile S. [UNESP]; Sabino, Joao Paulo J.; Fernandes, Romulo A. [UNESP] (Biomed Central Ltd., 2012)
Background: Recent studies have identified that a higher resting heart rate (RHR) is associated with elevated blood pressure, independent of body fatness, age and ethnicity. However, it is still unclear whether RHR can also be applied as a screening for other risk factors, such as hyperglycemia and dyslipidemia. Thus, the purpose of the presented study was to analyze the association between RHR, lipid profile and fasting glucose in obese children and adolescents.Methods: The sample was composed of 180 obese children and adolescents, aged between 7-16 years. Whole-body and segmental body composition were estimated by Dual-energy X-ray absorptiometry. Resting heart rate (RHR) was measured by heart rate monitors. The fasting blood samples were analyzed for serum triglycerides, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and glucose, using the colorimetric method.Results: Fasting glucose, TC, triglycerides, HDL-C, LDL-C and RHR were similar in both genders. The group of obese subjects with a higher RHR presented, at a lower age, higher triglycerides and TC. There was a significant relationship between RHR, triglycerides and TC. In the multivariate model, triglycerides and TC maintained a significant relationship with RHR independent of age, gender, general and trunk adiposity. The ROC curve indicated that RHR has a high potential for screening elevated total cholesterol and triglycerides as well as dyslipidemia.Conclusion: Elevated RHR has the potential to identify subjects at an increased risk of atherosclerosis development.
Keywords: Obesity; child; adolescent; metabolic dysfunctions; resting heart rate